DISTANCE COVERED BY A TECHNICAL SAFETY EMPLOYEE WORKING IN THE MINING INDUSTRY DURING A WORK SHIFT (DAILY, WEEKLY, MONTHLY) (Modern American Journal of Engineering, Technology, and Innovation, 2026)
In the article, was determined the movement distance of occupational safety personnel working in the mining industry. The distances traveled by occupational safety workers during a single workday (shift), weekly, and monthly were identified. The results were summarized and presented in a table. The study concluded with a summary.